Profiling athletes with disability the impact of sitting volleyball in quality of life among the national sitting volleyball team of the Philippines - Padlan, Nathan Christopher R. 2001-
Sitting Volleyball and other adaptive sports provide opportunities and improves quality of life for the PWD community. However, lack of opportunities and exposure to Sitting Volleyball leads to lack of awareness. This creates a barrier of systemic ableism against an inclusive and diverse community that the sport community should be. This thesis aims to determine which aspects of wellness are affected by Sitting Volleyball. This study will also be used to evaluate and describe the impact of sitting volleyball on the quality of life based on the physical, psychological, social, and environmental aspects of wellness targeted by the WHOQOL-BREF questionnaire. This study is a mixed method in a Survey Research design that aims to evaluate the effects of playing Sitting Volleyball on the quality of life of a Sitting Volleyball team through the use of WHOQOL-BREF Questionnaire and basic demographic questions for profiling. All participants (n= 19) answered the survey and results show high ratings in all domains of aspects of wellness enumerated in this study. Additionally, Sitting Volleyball participation was found to increase Environmental, Social, Physical, and Psychological aspects of wellness. In conclusion, there is a significant impact between Sitting Volleyball and quality of life within the population examined.